2014
DOI: 10.1016/j.ejcdt.2013.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of non invasive positive pressure ventilation in chronic obstructive pulmonary disease patients

Abstract: 27 patients diagnosed as chronic obstructive pulmonary disease (COPD) came with acute hypercapnic respiratory failure due to COPD and met the inclusion and exclusion criteria. They were managed by non invasive positive pressure ventilation (NIPPV). 21 cases showed success and 6 cases showed failure and were put on invasive mechanical ventilation within the first 24 h. It was shown that before initiation of NIPPV, the failed cases had significantly higher Body Mass Index (BMI) 34.7 compared to 28.1 in successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
(24 reference statements)
2
2
0
Order By: Relevance
“…NIPPV-failed patients stayed longer in ICU, had higher ICU and hospital costs, and higher in-hospital mortality [20]. Soliman and colleagues reported a 28.5% failure rate of NIPPV and immediate intubation in AECOPD patients at 24 hours from the initiation of therapy [21]. This is comparable to our results (30%) at 24 hours.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…NIPPV-failed patients stayed longer in ICU, had higher ICU and hospital costs, and higher in-hospital mortality [20]. Soliman and colleagues reported a 28.5% failure rate of NIPPV and immediate intubation in AECOPD patients at 24 hours from the initiation of therapy [21]. This is comparable to our results (30%) at 24 hours.…”
Section: Discussionsupporting
confidence: 79%
“…This is comparable to our results (30%) at 24 hours. They predicted NIPPV failure in patients with high BMI, lower initial pH, increased RR, higher PaCO2, and insignificant response to NIPPV after one hour [21].…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, a study in Egypt documented the success rate of NIPPV at 76% [15]. The result of the present study displayed a higher success rate as compared to the reported earlier studies, ranging between 50% and 80% [16,17]. In addition, NIPPV is effective, with a success rate of 89% in COPD subjects with respiratory acidosis with an arterial pH of 7.22 [18].…”
Section: Discussionsupporting
confidence: 60%
“…14,15 (Table 1) The present study group has a male preponderance (36/40) of 90% similar to other studies. 15,16,17 ( Table 2). The most common indication of NIV in our Study was acute exacerbation of chronic obstructive pulmonary disease (AE-COPD)90 % (Table 3) as in other studies 14,15,18 NIV was successful in 83.3% of patients in our study cohort of Acute exacerbation of COPD.…”
Section: Discussionmentioning
confidence: 99%